The Potential and Pitfalls of Collector Collaboration in Southeast Arizona. Issue 1 (February 2022) - Whisenhunt, Mary E.
ABSTRACT: In locales where much of the archaeological record has been destroyed or heavily impacted by pothunting and development, engaging with collector informants—including those who legally excavated sites on private property in the 1980s—can help fill crucial information gaps. However, such collaboration can pose ethical, and potentially legal, challenges. In this article, I outline research goals and results from a survey project in southeast Arizona's York-Duncan Valley, discuss the legal and ethical implications involved in working with former pothunters, and offer a critical evaluation of project practice. Finally, I offer a set of recommendations for those considering similar collaborations. I argue that the rejection of individuals who are knowledgeable about damaged or destroyed archaeological sites effectively silences the sites forever. Data acquired from former pothunters led to the identification and recording of 25 of 87 archaeological sites in the York-Duncan Valley. These individuals also served as interlocutors with others in the local community, helping us foster the trusted relationships necessary to promote site preservation on private property. A long-term engagement strategy that incorporates an assessment determining whether collector informants are responsible or responsive and that nurtures community involvement in preserving local archaeology offers a more productive course of action.